Sharia Financial Literacy for Generation Z - Tulasmi; Rakhmawati; Siti Latifah Mubasiroh (PT FORMOSA CENDEKIA GLOBAL, 2023)
The service activities comprised various stages, starting with the initial initiation and coordination with the leader, followed by observation, socialization, and the implementation of community service. This included conducting a pre-test, delivering the material in a classical format, facilitating a question and answer session, administering a post-test, as well as concluding with an evaluation and reporting phase. During the evaluation, the difference in values was assessed using the Wilcoxon test, with the statistical software Jamovi employed for this purpose. The results showed a significant increase in the Sharia financial literacy of students after completing the program. This successful service was a potential model for the government and other organizations to replicate, aiming to increase Sharia financial literacy and foster financial inclusion and economic development.